The Nazi perpetrator : postwar German art and the politics of the right - Jaskot, Paul B. (University of Minnesota Press, 2012)
Who was responsible for the crimes of the Nazis? Party leaders and members? Rank-and-file soldiers and bureaucrats? Ordinary Germans? This question looms over German disputes about the past like few others. It also looms over the art and architecture of postwar Germany in ways that have been surprisingly neglected. This book fundamentally reevaluates pivotal developments in postwar German art and architecture against the backdrop of contentious contemporary debates over the Nazi past and the difficulty of determining who was or was not a Nazi perpetrator.